In situ construction of intracellular supramolecular assemblies as an alternative strategy for protein degradation - Xiaoqian Hu; Qingxin Yao; Xiaobo Wu; Jiali Chen; Ruijia Zhang; Yan Zhao; Yuan Gao (Nature Communications)
Abstract Targeted protein degradation has emerged as a promising anticancer strategy. Bringing disease-related proteins into proximity with the degradation system is crucial but often hindered by the availability of suitable ligands for proteins of interest (POIs). In this study, we utilize the interactions between intracellular supramolecular nanofibers and certain guest proteins to establish a ligand-free strategy for protein degradation. As the enterokinase (ENTK)-instructed supramolecular assemblies interact with the histone protein H2B for its translocation, the tetrazine-bearing supramolecular nanofibers conjugate with a cereblon E3 ligase ligand to recruit CRBN and directly degrade wild-type H2B. Using the same bioorthogonal ligation, another reactive oxygen species (ROS)-induced supramolecular assemblies localize to mitochondria and efficiently degrade Cofilin-2. Both in situ formed intracellular supramolecular assemblies are dependent on cancer-related conditions (either overexpressed enzymes or overproduced ROS), owning the merit of cell selectivity. These assemblies synergize with bioorthogonal ligation to exhibit significant biological activities, including chemotherapeutic sensitization and induced apoptosis, thereby inhibiting cancer cell growth.